Amplification of the CD24 Gene Is an Independent Predictor for Poor Prognosis of Breast Cancer - Zhang, Peng; Zheng, Pan; Liu, Yang (Frontiers in Genetics, 2019)
CD24 is a glycosyl-phosphatidyl-inositol linked glycoprotein expressed in a broad range of cell types including cancer cells. Although it is overexpressed in nearly 70% of human cancers, copy number variation of the CD24 locus has not been reported for any cancer. Here we analyzed the genomics, transcriptomics, and clinical data of 1082 breast cancer (BRCA) samples and other cancer samples from the clinically annotated genomic database, The Cancer Genome Atlas (TCGA). The GISTIC2 method was applied to stratify the CD24 copy number, and Cox regression was performed to compare hazard ratio (HR) of CD24 overexpression, amplification and other traditional prognosis features for overall survival (OS). Our data demonstrated that CD24 amplification strongly correlated with its mRNA overexpression as well as TP53 mutant, cancer proliferation and metastasis features. In particular, CD24 amplification was enriched in basal-like subtype samples and associated with poor clinical outcome. Surprisingly, based on the univariate Cox regression analysis, CD24 overexpression (HR=1.62, P=0.010) and copy number amplification (HR=1.79, P=0.022) was more relevant to OS than TP53 mutant, mutation counts, diagnosis age and breast cancer subtypes. And based on multivariate survival analysis, CD24 amplification remained the most significant and independent predictor for worse OS (HR=1.88, P=0.015).